The effect of temperature on electrical energy production in double chamber microbial fuel cell using different electrode materials. (2021) - Hamed, Marwa S.; Majdi, Hasan S.; Hasan, Basim O.
Abstract: The use of fossil fuels, especially oil and gas, has accelerated in recent years, contributing to a global energy crisis in turn. To alleviate the ongoing global warming problem, green bioenergy is one way. Without any net carbon emissions, there is a strong need for new energy generation from renewable resources. In this work, the effect of temperature on the produced electrical energy in a double chamber microbial fuel cell was investigated. Nickel, Stainless steel, Brass, and Graphite electrodes were used. Yeast microorganisms (Saccharomyces cerevisiae) have been used at a concentration of 2 g/L to generate electric current and electrode generating capacities have been tested for temperature (25–40 °C). It was found that the current created for all the electrodes increases as the temperature increases, but at high temperatures, the activity of microorganisms decreases leading to a decrease in the current produced.